Ippaktuq Tasseok ("Harry") in deckhouse of whaling schooner Era, Cape Fullerton, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1904)
An Aivilik Inuit man identified as "Harry" [Ippaktuq Tasseok], is seated in a chair in front of a sail cloth backdrop in the deckhouse of the whaling schooner Era, January 25, 1904, Cape Fullerton, Hudson Bay, Canadian Arctic. Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo 197, #23. Harry is referred to in the North as Comer's [Captain George Comer] "mate," and was the leader of a group of Iglulik Inuit known as the Aivilik or Aivillingmiut. These Inuit of the west coast region of Hudson Bay were closely associated with Comer and the American whalers for many years. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. In his caption for this image, Comer describes Ippaktuq Tasseok as "our chief native."